Implementasi Pendidikan Karakter di Pondok Pesantren Daruz Zikri Manggilang Kecamatan Pangkalan Koto Baru Kabupaten Lima Puluh Kota - Fira Sastina; Darul Ilmi; Supriadi Supriadi; Jasmienti Jasmienti (Journal on Education, 2023)
The purpose of this study is to determine the implementation of character education at the Daruz Zikri Mangilang Islamic Boarding School, namely the implementation of character education on religious values and the value of responsibility at the Daruz Zikri Mangilang Islamic Boarding School and the supporting factors and inhibiting factors for the implementation of character education on religious values and the value of responsibility at the Islamic Boarding School. Daruz Zikri Mangilang This research is a qualitative descriptive study. The research location was at the Daruz Zikri Mangilang Islamic Boarding School, the informants for this research were the leadership, ustadz/ustadzah and students. This research was conducted in May 2022. The data collection techniques used were observation, interviews, and documentation. The data validity technique used is triangulation. Data analysis techniques are data reduction, data presentation, and data verification. The results of the study show that character education has been carried out at the Daruz Zikri Mangilang Islamic Boarding School. Implementation of character education on religious values and the value of responsibility at Daruz Zikri Manggilang Islamic Boarding School through the process of providing knowledge, planting, exemplary, habituation and creating a conducive educational environment so as to obtain effective results. The supporting factors of this Character Education are willingness, exemplary teacher, and the environment. While the inhibiting factors are potential or ability, facilities and infrastructure that are less supportive.